Anaphylactic contraction (Schultz-Dale reaction) of the bovine bronchial artery in vitro. - Alexander, D. I. (Nature Publishing Group, 1983)
Bronchial arteries from sensitized calves contracted on antigenic challenge in the absence and presence of selected anti-allergic drugs and autonomic agents in vitro. Anaphylactic reactivity was inhibited by tripelennamine, isoprenaline and aminophylline, and potentiated by indomethacin and dopamine. Disodium cromoglycate, compound FPL 55712 and ketanserin failed to inhibit anaphylactic contraction.